TLR7 Activation Accelerates Cardiovascular Pathology in a Mouse Model of Lupus - Elshikha, Ahmed S.; Teng, Xiang Yu; Kanda, Nathalie; Li, Wei; Choi, Seung-Chul; Abboud, Georges; Terrell, Morgan; Fredenburg, Kristianna; Morel, Laurence (Frontiers in Immunology, 2022)
We report a novel model of lupus-associated cardiovascular pathology accelerated by the TLR7 agonist R848 in lupus-prone B6.Sle1.Sle2.Sle3 (TC) mice. R848-treated TC mice but not non-autoimmune C57BL/6 (B6) controls developed microvascular inflammation and myocytolysis with intracellular vacuolization. This histopathology was similar to antibody-mediated rejection after heart transplant, although it did not involve complement. The TC or B6 recipients of serum or splenocytes from R848-treated TC mice developed a reactive cardiomyocyte hypertrophy, which also presents spontaneously in old TC mice as well as in TC.Rag-/- mice that lack B and T cells. Each of these cardiovascular lesions correspond to abnormalities that have been reported in lupus patients. Lymphoid and non-lymphoid immune cells as well as soluble factors contribute to lupus-associated cardiovascular lesions in TC mice, which can now be dissected using this model with and without R848 treatment.